Phyto-Fabrication, Structural Characterization and Antibacterial Properties of Hybanthus enneaspermus-Assisted Mn-Doped ZnO Nanocomposites - Kanmani Kannan; Sankareswaran Muruganandham; Archana Ganeshan; Rajiv Periakaruppan; Nithish Kathiravan; Sathyabama Narayanan (Eng)
Green synthesis of nanocomposites offers an eco-friendly and viable solution to overcome the limitations of conventional chemical and physical methods as it uses biological agents to act as reducing and stabilizing agents. The current study’s novelty is phyto-fabricated manganese (Mn)-doped zinc oxide (ZnO) nanocomposites using aqueous extract of H. enneaspermus by a biological method. Mn-doped ZnO nanocomposites were synthesized using manganese acetate and zinc acetate. The synthesized nanocomposites were characterized by XRD, FTIR, SEM, and EDX analysis. XRD shows the crystalline nature of nanocomposites with particle sizes of 30–40 nm, and FTIR reveals the presence of functional groups responsible for capping and stabilization. SEM analysis indicates spherical morphology with minor aggregation due to phytochemical interactions. EDX analysis of Mn-doped ZnO nanocomposites was used to verify the elemental composition, including Mn, Zn, O, and C. The anti-bacterial property of Mn-doped ZnO nanocomposites was assessed using the agar well-diffusion method against pathogens. The results of the anti-bacterial investigation proved that Mn-doped ZnO nanocomposites inhibit the growth of pathogens at different concentrations. The research concludes that the extract of H. enneaspermus acts as a capping and reducing agent in the synthesis process. The process can offer bio-compatible nanocomposites for new drug development against pathogens.